Different Time Schedules of Mifepristone and Misoprostol in Second Trimester Medical Abortion: A Comparative Study - Nalini Sharma; Ahanthem Santa Singh (Mashhad University of Medical Sciences, 2017)
Background & aim: Recently, the use of mifepristone followed by misoprostol after 36-48 h has been demonstrated to be an effective and safe method for the second trimester medical abortion. However, this regimen entails long total abortion time, and consequently increases the financial burden and anxiety in the patients. We hypothesize that one day interval would be also effective and can be used to provide the abortion care. Regarding this, the present study aimed to compare the effectiveness and safety of 24- and 36-hour intervals between the administration of mifepristone and misoprstol for second trimester abortion. Methods: This prospective comparative study was conducted on 70 females who opted for second trimester medical abortion between 12-20 weeks. Mifepristone (200 mg) was followed by sublingual misoprostol (800 mcg) after one and two days in the first and second groups, respectively. Four hours after the administration of 800 mcg misoprostol, all patients received 400 mcg sublingual misoprostol every 4 h (maximum of four doses in 24 h). For the purpose of the study, such parameters as the rate of successful abortion 24 h after the first dose of misoprostol, abortion duration, and the associated side effect profile were examined. Results: According to the results of the present study, the two-day interval (100%) was more effective than the one-day interval (91.4%) (P=0.021). Furthermore, the mean induction abortion duration was significantly less in the two-day regimen. However, the side effect profiles were comparable in both groups. Conclusion: As the findings of the present study indicated, both schedules of mifepristone and misoprostol were safe and effective in second trimester abortion. The 36-hour interval between mifepristone and misoprostol was more effective than the 24-hour interval. Furthermore, it had shorter abortion duration. We can individualize the patient care by offering a one-day interval regimen since it is more effective and has less duration for total abortion.